Determination of binary asteroid orbits with a genetic-based algorithm - Vachier, F; Berthier, J; Marchis, F (Astronomy and astrophysics (Berlin), 2012)
The authors implemented a new approach for determining the mutual orbits of directly-imaged multiple asteroids using a genetic-based algorithm. This approach was applied to several known binary asteroid systems 22 Kalliope, 3749 Balam, and 50 000 Quaoar observed with adaptive optics (AO) systems and Hubble Space Telescope (HST). This statistical method is fast enough to permit the search for an orbital solution across a large parameter space and without a priori information about the mutual orbit. From 10 years of observation, they derived an orbital solution for Linus, companion of 22 Kalliope, with an accuracy close to the astrometric limit provided by the AO observations, assuming a purely Keplerian orbit. HST astrometric observations of Weywot, companion of the trans-Neptunian object 50 000 Quaoar, were used to derive its mass and its bulk density, which appears to be higher than the density of other TNOs. Finally, they derived a bundle of orbital solutions for 3749 Balam, with equally good fits, from the limited set of astrometric positions.